Care of the psyche : a history of psychological healing - Jackson, Stanley W., 1920- (Yale University Press, 1999)
"In this book, a distinguished historian of medicine surveys the basic elements that have constituted psychological healing over the centuries. Dr. Stanley W. Jackson shows that healing practices, whether they come from the worlds of medicine, religion, or philosophy, share certain elements that transcend space and time." "Drawing on medical writings from classical Greek and Roman times to the present, as well as on philosophical and religious writings, Jackson shows that the basic ingredients of psychological healing - which have survived changes of name, the fall of their theoretical contexts, and the waning of social support in different historical eras - remain essential factors in our modern psychotherapies and in healing contexts in general."--Jacket